2023
DOI: 10.1111/jpi.12906
|View full text |Cite
|
Sign up to set email alerts
|

The mammalian gastro‐intestinal tract is a NOT a major extra‐pineal source of melatonin

David J. Kennaway

Abstract: In 1992, a paper reported that the melatonin content of the rat duodenum was 24 000 ± 2000 pg/g tissue (range: 4000–100 000 pg/g) while the pineal melatonin content was 580 000 ± 36 000 pg/g. The data has been used for the last 30 years to infer that the gut produces 400 hundred times more melatonin than the pineal gland and that it is the source of plasma melatonin during the daytime. No‐one has ever challenged the statement. In this review, evidence is summarised from the literature that pinealectomy elimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 98 publications
0
1
0
Order By: Relevance
“…In general, the concentration of extra-pineal MLT is reported to be several orders of magnitude higher than that of the circulating pool derived from the pineal gland. Nevertheless, it has recently been found that the gastrointestinal tract is not a major source of extra-pineal MLT, as was formerly believed [ 5 ]. It is, therefore, possible that some of the early studies in this field overestimated the MLT content because of methodological flaws.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the concentration of extra-pineal MLT is reported to be several orders of magnitude higher than that of the circulating pool derived from the pineal gland. Nevertheless, it has recently been found that the gastrointestinal tract is not a major source of extra-pineal MLT, as was formerly believed [ 5 ]. It is, therefore, possible that some of the early studies in this field overestimated the MLT content because of methodological flaws.…”
Section: Introductionmentioning
confidence: 99%